COVID-19-related social support service closures and mental well-being in older adults and those affected by dementia: a UK longitudinal survey. Issue 1 (17th January 2021) - Giebel, Clarissa; Pulford, Daniel; Cooper, Claudia; Lord, Kathryn; Shenton, Justine; Cannon, Jacqueline; Shaw, Lisa; Tetlow, Hilary; Limbert, Stan; Callaghan, Steve; Whittington, Rosie; Rogers, Carol; et al.
Abstract : Background: The COVID-19 pandemic has had a major impact on delivery of social support services. This might be expected to particularly affect older adults and people living with dementia (PLWD), and to reduce their well-being. Aims: To explore how social support service use by older adults, carers and PLWD, and their mental well-being changed over the first 3 months since the pandemic outbreak. Methods: Unpaid dementia carers, PLWD and older adults took part in a longitudinal online or telephone survey collected between April and May 2020, and at two subsequent timepoints 6 and 12 weeks after baseline. Participants were asked about their social support service usage in a typical week prior to the pandemic (at baseline), and in the past week at each of the three timepoints. They also completed measures of levels of depression, anxiety and mental well-being. Results: 377 participants had complete data at all three timepoints. Social support service usage dropped shortly after lockdown measures were imposed at timepoint 1 (T1), to then increase again by T3. The access to paid care was least affected by COVID-19. Cases of anxiety dropped significantly across the study period, while cases of depression rose. Well-being increased significantly for older adults and PLWD from T1 to T3. Conclusions: Access to social support services has been significantly affected by the pandemic, which is starting to recover slowly. With mental well-being differently affected across groups, support needs to be put in place to maintain better well-being across those vulnerable groups during the ongoing pandemic.